Constraints to the timing of India-Eurasia collision determined from the Indus Group: a reassessment - Henderson, Alexandra L; Najman, Yani; Parrish, Randall R; Carter, Andrew; Boudagher-Fadel, Marcelle; Foster, Gavin; Garzanti, Eduardo; Andò, Sergio (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1266 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.64